SPEECH ACTS ANALYSIS UTTERED BY MOTHER GOTHEL IN “TANGLED" (2010) - Lusi Nuryanti, Lusi Nuryanti (ReALL - Research on Applied Linguistics and Literature, 2024)
This study aims to examine the illocutionary speech acts performed by the character Mother Gothel in the film Tangled (2010). The research seeks to identify and analyze the various forms and types of illocutionary speech acts used by Mother Gothel. To achieve this, the study utilizes Austin’s (1962) theory, which divides speech acts into three components: locutionary, illocutionary, and perlocutionary, alongside Searle’s (1974) theory, which categorizes speech acts into five distinct types: assertive, directive, commissive, expressive, and declarative. The research employs a qualitative descriptive method, analyzing data sourced from both the film and its script. The findings reveal a total of 90 illocutionary speech acts performed by Mother Gothel, classified by both form and type. In terms of sentence form, the study identified 47 declarative, 13 interrogative, and 31 imperative speech acts. By type, the study found 13 assertive, 59 directive, 8 commissive, and 10 expressive acts. Notably, among the five types of illocutionary speech acts, declarative illocutionary acts were absent in Mother Gothel's speech. The study concludes that while declarative speech acts were not found, the film features various examples of interrogative, imperative, and other illocutionary acts, including assertive, directive, commissive, and expressive types. This analysis provides insights into how Mother Gothel's character utilizes these speech acts in the film as an antagonist character.